2016
DOI: 10.1016/j.rppnen.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of bronchiectasis: A review of 20 years of experience

Abstract: Although the number of patients with bronchiectasis referred for surgical treatment has decreased, pulmonary resection still plays a significant role. Surgical resection of localized bronchiectasis is a safe procedure with proven improvement of quality of life for the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…A meta-analysis revealed a mortality rate of 1.5% and an improvement in symptoms in 66.5% of patients 145 . In one study, quality of life after 1 year of follow-up was reported as excellent in 73.3% of patients and as unchanged in only 8.3% 150 . One group of authors also demonstrated that quality of life improved and exercise capacity was preserved in selected surgical patients 151 .…”
Section: Therapeutic Management Of Stable Patientsmentioning
confidence: 99%
“…A meta-analysis revealed a mortality rate of 1.5% and an improvement in symptoms in 66.5% of patients 145 . In one study, quality of life after 1 year of follow-up was reported as excellent in 73.3% of patients and as unchanged in only 8.3% 150 . One group of authors also demonstrated that quality of life improved and exercise capacity was preserved in selected surgical patients 151 .…”
Section: Therapeutic Management Of Stable Patientsmentioning
confidence: 99%
“…Advances in the medical management of bronchiectasis have made surgical intervention less common. However, in the case of highly-localized disease, resection of affected lobes can improve a patient's QOL and reduce the frequency of antibiotic courses (99,100). Indication for surgical resection of an affected lobe of the lung include persistent failure of medical management and hemoptysis, and current expert consensus recommends limiting lobectomy to those patients in whom maximal medical management has been trialed (61,100).…”
Section: Surgical Managementmentioning
confidence: 99%
“…2 In patients with localised disease, recent reviews suggest that the removal of the permanently damaged areas of the lung can result in significant symptom resolution and an improved quality of life. 75, 76 In a meta-analysis of 38 studies covering 5541 patients who had surgical resection for management of bronchiectasis, operative morbidity and mortality rates were 16.7% and 1.5%, respectively. 76 …”
Section: Overall Goals Of Treatmentmentioning
confidence: 99%